Fecal organisms in supplied and domestically treated waters in Dhaka: insights from Maghbazar, Rampura, Badda and Bashundhara - Jhilik, Apsara Dey (Brac University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Microbiology, 2019.